Effective reuse of red mud as supplementary material in cemented paste backfill: Durability and environmental impact. (18th April 2022) - Wang, Zhikai; Wang, Yiming; Wu, Libo; Wu, Aixiang; Ruan, Zhuen; Zhang, Minzhe; Zhao, Runkang
Highlights: The durability and leaching behavior of rm-cpb were studied systematically. The UCS of RM-CPB was investigated by orthogonal experiment. The environmental impact of RM-CPB was studied by three different leaching methods. Abstract: Red mud (RM) is a potential supplementary backfill material. However, little is known about cemented paste backfill (CPB) preparation from reused RM. Here, the feasibility of Bayer RM in CPB technology is discussed to expand the utilization of solid waste. With Bayer RM, Fly ash (FA), and cement as raw materials, the strength performance of Bayer RM in cemented paste backfill (RM-CPB) was evaluated by the orthogonal experiment method, and the optimal ratio of RM-CPB was determined. The effects of slurry concentration, mixing ratio of RM to FA, and the cement dosage on uniaxial compressive strength (UCS) were studied. Its durability, microstructure, permeability, and environmental properties were investigated. The experimental results show that the strength of the optimum proportion reached 1.25 MPa and 2.37 MPa after curing for 3 d and 28 d respectively and meet the mine design standard when the ratio of RM-CPB is: 60% of the slurry concentration, the RM: FA is 3:2, and the dosage of cement is 5%. RM-CPB material has good durability, and the main hydration products are C-S-H gel, ettringite, and gmelinite, which is conducive to the development of UCS of the backfill material. Meanwhile, the permeability k20 of RM-CPB is only 6.005 × 10 -6 cm/s, indicating that the material has few internal pores, which can effectively prevent external water intrusion. The leaching test results showed that both the heavy metal concentration and pH value of the leachate were within the range specified in the Chinese standard (DZ/T 0290–2015), and it was found that the effect of the three ion leaching tests is successive: toxicity leaching test > immersion test > eluviation test. The comprehensive analysis found that the reuse of Bayer RM as a supplementary cemented paste backfill material provides a new idea for the large-scale utilization of industrial solid waste.